Dengue fusion peptides in interaction with model membranes – a fluorescence study - Olivier, Danilo da Silva; Cespedes, Graziely Ferreira; Pazin, Wallance Moreira; Cilli, Eduardo Maffud; Ito, Amando Siuiti (Eclética Química, 2021)
Dengue fever is a widespread infectious disease caused by Dengue viruses and responsible for millions of cases per year. One of the key steps during the infection is the fusion between the cell membrane and the lipidic bilayer of the virus, done by the glycoprotein envelope. At the tip of the envelope there is a fusion peptide widely conserved among the four known virus serotypes. Here dengue fusion peptides were studied in buffer solution and interacting with model membranes using fluorescence techniques. Peptides have the tryptophan residue exposed to aqueous environment when in buffer, while is exposed to a hydrophobic environment when interacting with negatively charged vesicles, as shown by the blue shift of fluorescence emission and increase in the lifetime decay. Fluorescence anisotropy results confirm that the residue is in a more restrictive environment when interacting with vesicles. Finally, fluorescence correlation spectroscopy results support the importance of electrostatic interaction, showing that dengue peptide promotes a significant increase in diameter of negatively charged vesicles, compared to the absence of effect in the size of neutral vesicles.